A Study on Flouting and Hedging Maxims Used by the Main Characters on “Daddy Day Camp” - Maria Helmi (Linguistic, English Education and Art (LEEA) Journal, 2022)
This research focused on analyzing flouting and hedging maxims used by the main characters on "Daddy Day Camp". The purposes of this research were to investigate and analyze how the maxims are flouted and hedged by the main characters on "Daddy Day Camp". Qualitative method was used in this research because the data were in the form of words rather than that of numbers and statistics. The data were taken from the utterances spoken by the main characters on "Daddy Day Camp". After the data are collected, they are classified and analyzed based on Grice’s Cooperative principle theory. This research found many maxims of cooperative principle which were flouted and hedged by the main characters on "Daddy Day Camp", especially the maxim of quality and quantity. On the other hand, this research also found that the utterances spoken by the main characters hedged the maxims of cooperative principle. There were some utterances which hedge the maxim of quality and relevance because the utterances which were spoken by the main characters are not totally accurate but seem informative, well founded and relevant. Keywords: Daddy Day Camp, Flouting Maxim, Hedging Maxims